Electrochemical and chromatographic methods for synthesising and analysing aryl phosphonium salts - Almudhady, Saddam Hussein (2018)
This thesis concerns the synthesis and analysis of aryl phosphonium salts (ArPSs). The first part of the thesis describes the analytical electrochemistry of triphenylphosphine, diphenyliodonium trifluoromethanesulfonate, and tetraphenylphosphonium trifluoromethanesulfonate at glassy carbon electrodes using cyclic voltammetry where all potentials were referenced to Fc/Fc+ couple. The second part of the thesis describes the electrochemical synthesis of aryl phosphonium salts using graphite electrodes. The third part of the thesis describes the development of reverse phase-high performance liquid chromatography (RP-HPLC) methods for analysing and purifying ArPSs. The analytical electrochemical studies of triphenylphosphine (Ph3P) revealed two oxidation peaks at +0.79 V and +0.95 V. On the other hand, three reduction peaks were observed for tetraphenylphosphonium trifluoromethanesulfonate ([Ph4P][OTf]) at the same working electrode. For diphenyliodonium trifluoromethanesulfonate ([Ph2I][OTf]), two reduction peaks were observed at –1.06 V and –1.37 V. [Ph4P][OTf] was electrosynthesised using carbon electrodes with a conversion of about 30% and triphenyl(pyridin-2-yl)phosphonium triflate ([Ph4Ppy][OTf]) was electrosynthesised with a conversion yield of about 59.50% (according to 31P NMR spectroscopy). Chapter Four illustrates how a wide range of RP-HPLC methods were established. Firstly, a gradient elution HPLC method for separating ArPSs from starting materials was developed using an ammonium formate buffer (pH = 6.0) and acetonitrile (the organic modifier) in the mobile phases and an analytical column (Waters - SunFire C18 column, pore size of 100 Å, particle size of 3.5 µm, 2.1 mm X 30 mm). Complete separation of [Ph2I][OTf], [Ph4P][OTf], Ph3P=O, and Ph3P was achieved in 5.5 minutes. The resolution between [Ph4P][OTf] and triphenylphosphine oxide (Ph3P=O) (the closest two peaks) was 1.82. By replacing acetonitrile with methanol (the organic modifier), a better resolution between [Ph4P][OTf] and Ph3P=O of 5.01 was obtained. Moreover, this resolution was then further increased to 5.89 when a bigger column (Column250, Discovery® HS C18 column, 120 Å, particle size of 5 µm, and 4.6 mm X 250 mm dimensions) was used. This was key step towards the quantitative separation of ArPSs from their mixtures (after completing their preparation process). This quantitative separation was successfully achieved with an excellent recovery of 93.3% and 94.4% when different successive amounts of 200 µg and 440 µg were injected, respectively. Finally, quantitative chromatographic analysis of the ArPSs prepared from electrochemical synthesis route revealed significantly lower yields than those determined using NMR spectroscopy. These analyses revealed that iodonium salts are co-precipitated with phosphonium (due to the similarity in the chemistry of iodonium and phosphonium species) during synthesis and separation methods are required during the synthesis of these compounds. In addition, these analyses show that the developed chromatographic methods can be used for analysing and purifying ArPSs.